Smart Bagan Ikan Berbasis IoT dan GPS untuk Peningkatan Hasil Tangkap Nelayan - Dermawan, Aulia Agung; Lawi, Ansarullah; Candra, Joni Eka (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Buluh Island, one of the coastal areas in Batam City, faces serious challenges in the fisheries sector due to the use of traditional fishing methods, which result in high operational costs, the risk of catch theft, and low productivity. This Community Service Program (PKM) offers a solution by applying GPS- and IoT-based Smart Fishing Technology, integrated with solar panels for energy. This technology enables fishermen to monitor the condition of their nets in real time, detect fish using sonar, and minimize travel, thereby reducing fuel consumption. Method: The program takes a participatory approach, involving fishermen from the socialization stage, training, device installation, and evaluation. Results: The implementation shows decreased operational costs, increased net safety against theft, and higher catch yields, which impact fishermen's income. Additionally, the program has successfully produced financial management training, video documentation, scientific publications, intellectual property rights, and educational posters. Kesimpulan: Smart Bagan is expected to be replicated in other coastal areas to support the sustainable welfare of fishing communities, in line with the achievement of SDGs 1, 2, 8, and 14.